Prevenindo fracasso escolar: comparando o autoconceito e desempenho acadêmico de filhos de mães que trabalham fora e donas de casa. - D'Affonseca, Sabrina Mazo (Universidade Federal de São Carlos, 2005)
Researchers in the area of special education have shown that various factors outside the school system can lead children to develop learning problems. Poor quality family relationships, for example, can interfere with the healthy development of the various facets of a child s self concept which, in turn, can lower the child s academic achievement. As such, many criticisms are made concerning the way that parents especially mothers - divide their attention between their children and other involvements. Presently, most married women fall into one of two categories: some dedicate the great majority of their time to caring for their family and homes, while others divide their time between their family, homes and paid employment. Both options bring advantages and disadvantages to the task of parenting. For working mothers, the great amount of time required to meet both family and professional obligations is a source of stress, which can compromise the quality of parent-child relationships. On the other hand, in many families in which the mother is a housewife, financial resources are fewer and the women have lower selfesteem and poorer health than women who have paid employment, which can reduce the quality of their parenting behaviors. The objectives of this study were to: a) adapt existing instruments to evaluate work conditions, psychological wellbeing and the mothers involvement in bringing up their children; b) compare housewives and women who have paid employment with respect to the frequency of various types of involvements with their children; and c) investigate the relationship between the frequency of these interactions and three measures that reflect the adequacy of certain aspects of their children s development (self-concept, academic achievement and the children s perceptions of the mother-child relationship). Participants included 60 mother-child pairs -- 23 mothers with paid employment and 37 housewives. The average age of the mothers was 36.5 years. The children were in either fifth or sixth grade, with an average age of 11.9 years. The mothers responded to the Mother s vision about her family interaction and well being Questionnaire , and the children were evaluated using Portuguese versions of the Academic Achievement Test , the Self-Description Questionnaire I (SDQI) and the Mother-Child Relationship Questionnaire Child´s Vision . With respect to the mothers, both groups reported that they make frequent use of the majority of the parenting behaviors that lead to healthy family relationships, with very few statistically significant differences appearing between the two groups. With respect to the children, there were no statistically significant differences between those whose mothers were housewives and those whose mothers had paid employment, in terms of their academic achievement, selfconcept or their evaluations of the frequency of their interactions with their mothers. These results indicate that there was no relationship between these three measures of the children s wellbeing and their mothers employment status. However, correlations showed that the frequency of some types of maternal interaction make a positive contribution to the development of their children s academic self-concept, which, in turn, is positively related to their academic achievement. Thus, the frequency of the mothers involvement in their children s lives, in and of itself, and not her status as a housewife or a working mother, seems to be an important factor for the development of a positive selfconcept and achievement of academic success, among their children.
Keywords: Educação Especial; Autoconceito; Mães e filhos - relações; Rendimento escolar; Mothers with paid employment; Housewives; Mothers involvement; Academic achievement; Self-concept; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL